Upconversion fluorescence spectroscopy of Er3+/Yb3+-doped heavy metal Bi2O3-Na2O-Nb2O5-GeO2 glass - Oliveira, A. S.; de Araujo, M. T.; Gouveia-Neto, A. S.; Sombra, ASB; Neto, JAM; Aranha, N. (American Institute of Physics (AIP), 1998)
Upconversion fluorescence emission of Er3+/Yb3+-doped Bi2O3-Na2O-Nb2O5-GeO2 heavy metal glass samples excited at 1.06 mu m is experimentally investigated. The results reveal the existence of intense emission bands centered around 520, 545, and 655 nm. The germano-niobate based host glass presents high transparency in the region of 400-2700 nm, the capability of incorporating high dopant concentrations, high melting temperature, and large resistance to atmospheric moisture. The observed intensity of the green fluorescence emission, suggested that the niobium based host glass material plays an important role in the efficiency of the upconversion process. Emission lines centered at 425, 483, 503, 608, and 628 nm were also observed. (C) 1997 American Institute of Physics.